Adalimumab dose tapering in patients with rheumatoid arthritis who are in long-standing clinical remission: results of the phase IV PREDICTRA study. Issue 8 (13th May 2020) - Emery, Paul; Burmester, Gerd R; Naredo, Esperanza; Sinigaglia, Luigi; Lagunes, Ivan; Koenigsbauer, Franziska; Conaghan, Philip G
Abstract : Objective: To investigate the association between baseline disease activity and the occurrence of flares after adalimumab tapering or withdrawal in patients with rheumatoid arthritis (RA) in sustained remission. Methods: The PREDICTRA phase IV, randomised, double-blind (DB) study (ImP act of R esidual Inflammation Detected via Imaging TE chniques, D rug Levels, and Patient Characteristics on the Outcome of Dose TaperI ng of Adalimumab in C linical Remission Rheumatoid ArT hritis (RA ) Patients) enrolled patients with RA receiving adalimumab 40 mg every other week who were in sustained remission ≥6 months. After a 4-week, open-label lead-in (OL-LI) period, patients were randomised 5:1 to DB adalimumab taper (every 3 weeks) or withdrawal (placebo) for 36 weeks. The primary endpoint was the association between DB baseline hand and wrist MRI-detected inflammation with flare occurrence. Results: Of 146 patients treated during the OL-LI period, 122 were randomised to taper (n=102) or withdrawal (n=20) arms. Patients had a mean 12.9 years of active disease and had received adalimumab for a mean of 5.4 years (mean 2.2 years in sustained remission). Overall, 37 (36%) and 9 (45%) patients experienced a flare in the taper and withdrawal arms, respectively (time to flare, 18.0 and 13.3 weeks). None of the DB baseline disease characteristics or adalimumab concentration was associated with flare occurrence after adalimumab tapering. Approximately half of the patients who flared regained clinical remission after 16 weeks of open-label rescue adalimumab. The safety profile was consistent with previous studies. Conclusions: Approximately one-third of patients who tapered adalimumab versus half who withdrew adalimumab experienced a flare within 36 weeks. Time to flare was numerically longer in the taper versus withdrawal arm. Baseline MRI inflammation was not associated with flare occurrence. Trial registration number: NCT02198651, EudraCT 2014-001114-26 .